(untitled) (Third Sector Social Economic Review, 2015)
The purpose of this study is to analyze why the non-governmental organizations became an active participation assets in the governance process. Notion of government, especially gained importance after coming up state idea, is subject to searches of public management’s rationalizing by developing according to economic and socio-cultural factors. New public management paradigm includingimplement of new government assumptions presents governance process andregulates governance phenomenon as response of searches of activeness and democratic in axle of participation. As governance model with poly-actors, governance process is a government idea in which not only public but also private sector and non-governmental organizations are embodied in management. Participation in management of non-governmental organizations are assessed as an important development of realizing participatory democracy. In this study, firstly, historical process of government idea and transition of new public management to classic public management are going to mention and then non-governmental organizations as participation factor in management process and roles in management of non-governmental organizations are going to referred. In this, management refers just public management, so private sector is going to be out of scope, for management phenomenon is discussed as government or public management in this study.